*This preview shows
pages
1–11. Sign up
to
view the full content.*

This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **( 29 ln u u d du a a a dx dx = So far today we have: u u d du e e dx dx = ( 29 ln u u d du a a a dx dx = Now it is relatively easy to find the derivative of . ln x ln y x = y e x = ( 29 ( 29 y d d e x dx dx = 1 y dy e dx = 1 y dy dx e = 1 ln d x dx x = 1 ln d du u dx u dx = To find the derivative of a common log function, you could just use the change of base rule for logs: log d x dx ln ln10 d x dx = 1 ln ln10 d x dx = 1 1 ln10 x = The formula for the derivative of a log of any base other than e is: 1 log ln a d du u dx u a dx = u u d du e e dx dx = ( 29 ln u u d du a a a dx dx = 1 log ln a d du u dx u a dx = 1 ln d du u dx u dx =...

View
Full
Document